Amplitude‐phase discontinuity calibration for phased array radar in varying jamming environment. Issue 7 (1st September 2014) - Meng, Ziqiang; Li, Yachao; Song, Xiufeng; Xing, Mengdao; Bao, Zheng
Abstract : The amplitude‐and‐phase error (APE) between phased array channels is notorious in radar signal processing. This error can cause an inaccurate estimate of unknown steering vector of the target echo signal and eventually result in amplitude‐phase discontinuity of the phased array output. Thus, how to handle the APE is a meaningful problem, particularly for the varying jamming environment, of which the signal‐to‐noise ratio is very low. In this study, the authors have developed a new method to obtain real‐time amplitude and phase differences between two consecutive weight update periods based on the accurate estimation of steering vector. Such differences can be used to obtain a real‐time weight vector with negligible amplitude‐phase distortions, and hence improves the phased array signal‐processing performance. The proposed method is very flexible: it works well in different array configurations, such as linear, rectangular and Y‐shape arrays, and can be efficiently implemented in any eigenstructure‐based direction‐of‐arrival system.